INCLUSION EDUCATION, A STUDY AND CRITICAL ANALYSIS WITH THE DIMENSIONS OF INCLUSION INDEX IN SMPN 28 SURABAYA (Proceedings of International Conference on Special Education, 2019)
Inclusive education has now begun to develop in many schools in Indonesia, especially in Surabaya. Inclusive education is the development of education that can serve all characters of students without discrimination in Indonesia. The general objective of this study is to describe and analyze the management of inclusive education in SMP Negeri 28 Surabaya to measure the quality of schools in managing inclusive education using the inclusive index dimension. Management of the organizers of inclusive schools is based on appointments from the central government which are forwarded to the Surabaya City government. Management of identification and assessment of students is done at the beginning of the students entering, the assessment results are carried out to determine the abilities, weaknesses and needs of special needs students, which will determine the making of learning curriculum modification programs covering aspects of objectives, sources, materials, media, schedules , and assessment. Changes in curriculum modification are intended so that students with special needs can be properly served in accordance with the characteristics and needs of each student. From the curriculum modification will produce individual learning programs. management of learning is carried out collaboratively between subject teachers, GPK, BK teachers, and homeroom teachers to obtain optimal learning conditions. Management of assessment takes into account the circumstances of special needs students and regular students.